Assessing the Financial Performance of Digital Sharia Bank at Bank Aladin Syariah: EVA and MVA Approach - Siska, Elmira; Sebastian, Dante Rio; Islami, Vina (Jurnal Ilmiah Ekonomi Islam, 2024)
Bank Aladin Syariah is Indonesia's first completely digital bank that follows Sharia rules. This bank held its initial public offering on January 22, 2021. Apart from using financial ratios, the bank's financial performance may be assessed using the economic value added (EVA) and market value added (MVA) approaches. These two methods function to complete financial performance analysis through financial ratios and find the true value of company performance. This research aims to determine and analyze the financial performance of Bank Aladin Syariah using the EVA and MVA methods. The research design of this study uses non-statistical quantitative methods with a descriptive approach. The data used in the research is secondary data derived from financial reports for 2019-2023. This data is downloaded from the bank's website. The research results show that operation of Bank Aladin Syariah succeeded generate economic value added remarked by positive EVA in 2019, 2020, and 2022. Meanwhile, in 2021 and 2023 Bank Aladin Syariah fail to give more economic value through its activities. This is evident from a negative EVA score. Since Bank Aladin Syariah conducted its IPO, the bank has succeeded in providing added value through growth in the market capitalization value of shares issued which is indicated by a positive MVA during 2021 - 2023.